Receipt and Sharing of Information to Improve Knowledge About Living Donor Kidney Transplant among Transplant Candidates with Advanced Chronic Kidney Disease. (September 2022) - Mohottige, Dinushika; Davenport, Clemontina; Lee, Hui-Jie; Ephraim, Patti; DePasquale, Nicole; Cabacungan, Ashley; Barrett, Tyler; McElroy, Lisa; Pendergrast, Jane; Diamantidis, Clarissa J.; Boulware, L. Ebony
Introduction: Knowledge about living donor kidney transplant (LDKT) is associated with greater access. Yet, little is known about factors associated with high living donor transplant knowledge.Research Questions: Is receipt of LDKT information from health professionals or sharing information with family and friends associated with higher knowledge?Design: We conducted a cross-sectional analysis of data from preemptive LDKT candidates, which assessed knowledge, receipt of information about living donation from health professionals, and history of having shared living donor information with family members or friends. In multivariable logistic regression models adjusting for participants' age, race, and total household income, we quantified the association of high knowledge with receipt of living donation information from health professionals and sharing of this information with family/friends.Results: Among 130 participants, the median (IQR) age was 59.5 (52.0–65.0) years, 60% were female, 47.7% were Black, and 49.2% had a high school education or less. Over half (55.4%) had high LDKT knowledge. Nearly one third reported having received living donor information (33.1%) or sharing the information with family/friends (28.5%). After adjustment, those who received (vs. did not receive information) and shared information with family/friends had 3-fold higher odds of high LDKT knowledge (3.05 [1.24, 8.08]). Individuals who received LDKT information (vs. did not) from health professionals had 4-fold higher odds of high LDKT knowledge (adjusted OR [95% CI]: 4.01 [1.49, 12.18].Conclusions: Receipt of living donation information from health professionals and sharing this information with family/friends were associated with high LDKT knowledge.